Relevansi Penerapan Teori Hukum terhadap Perlindungan Nasabah Perbankan yang Dirugikan oleh Transaksi Internet Banking (Analisis Teori Hukum Positif dan Teori Utilitas) - Yacob, Ardyansyah; Idham, Idham; Erniyanti, Erniyanti (Kajian Ilmiah Hukum dan Kenegaraan, 2022)
Purpose: The purpose of writing this journal is to find out the legal arrangements for the protection of banking customers who are harmed by internet banking transactions, and to know the relevance of the application of legal theory to the protection of banking customers who are harmed by internet banking transactions. Method: The method used is a normative approach, namely through library research, and an empirical approach, namely through field research by conducting a series of interviews with respondents and informants to obtain field data. Result: The results of the study show that the legal arrangements for protecting banking customers who are harmed by internet banking transactions are regulated in Law Number 8 of 1999 concerning Consumer Protection, Bank Indonesia Regulation Number 10/10/PBI/2008 concerning Settlement of Customer Complaints, Regulations of the Financial Services Authority Number 1/POJK.07/2013 concerning Consumer Protection in the Financial Services Sector, and Bank Indonesia Circular Letter Number 9/30/DPNP concerning Implementation of Risk Management in the Use of Information Technology by Commercial Banks. The relevance of the application of legal theory to the protection of banking customers who are harmed by internet banking transactions. The application of law through legal theory in Indonesia from the perspective of philosophy of science can be seen from the legal protection that occurs. Legal protection as an effort to uphold justice, customers can claim compensation from the bank if there is a system error caused by an internet banking transaction, but this provision does not apply if the error is caused by the act or omission of the customer and the bank is required to warn customers about the risks of using the internet banking